Epithelioid sarcoma of the tongue. Issue 10 (October 1997) - Leroy, X; Delobelle, A; Lefebvre, J L; Cabaret, V; Bloget, F; Vilain, M O
Abstract : A case of epithelioid sarcoma in the tongue is reported. The patient, a 35 year old woman, presented with a non-ulcerated painful lesion of the tongue. Microscopically, the tumour was characterised by multiple coalescent nodules with central geographic necrosis infiltrating the lingual muscle. The tumour cells were epithelioid with abundant eosinophilic cytoplasm and atypical nuclei. Immunohistochemically, the tumour cells stained for vimentin, keratin, and epithelial membrane antigen. These morphological and immunohistochemical appearances led to the diagnosis of epithelioid sarcoma of the tongue. Seven years later, the patient died with metastatic dissemination to the scalp, lungs, and brain. No case of epithelioid sarcoma arising in the tongue has been described previously.